Optimalisasi Pengelolaan Dana Umat Pada Masyarakat Melayu - Kuswandi, Dedi; Panorama, Maya (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The purpose of the research is to knowing the role of the National Amil Zakat Agency and to find out how much public trust in institutions that manage people's funds other than BAZNAS. This research was conducted using descriptive qualitative methods. To get this information, it can be done with several techniques, one of which is through observation activities, direct interview activities or dialogue processes carried out and through documentation studies so that all information can be obtained properly. Regarding the technique in processing the data, it is done by reducing the data and then presenting it and drawing conclusions according to the research carried out. As a party that has broader authority over other zakat collection bodies and institutions, the role of BAZNAS is very important and vital, especially in ensuring collaboration and cooperation between stakeholders. Then examine in general that many people do not trust amil zakat institutions or bodies so that much of the distribution is made directly to people who receive the zakat rather than being distributed to existing amil zakat bodies.